(untitled) - Clayton, Richard; Richard Clayton; Hugh Tomlinson (Oxford,New York, 2003)
This major new practitioner text provides comprehensive and systematic treatment of human rights law and practice in the UK, including detailed analysis of the impact of the incorporation of the European Convention on Human Rights into domestic law by the Human Rights Act 1998. Regular paperback supplements will be published to keep the book fully up to date with relevant case-law and related legislation as the implementation of the new Act proceeds
Keywords: Civil rights; Human rights